Przepis na wychowanie w świetle korespondencji rodziny Bnińskich - Czerniecka-Haberko, Anna; Studnicka-Mariańczyk, Karolina (Biuletyn Historii Wychowania, 2019)
An analysis has been carried out of several dozen letters written between 13 August 1876 and 5 May 1890 by Roman Bniński (the father), addressed mainly to his son, Roman. The analysed letters allow us to gain some insight, no matter how minimal, into the father’s attitude towards his son, which is expected to shape his offspring. Not surprisingly, the correspondence reflects acceptance, cooperation, reasonable freedom and recognition of the child’s rights. In general, letters are a direct source presenting a family’s everyday life, relations between family members, family affinities and relations with neighbours, acquaintances and friends... This is all reflected in the letters written by Roman Bniński to his son. Like all direct written sources, the letters provide a new image of the landed gentry, which is confronted with its stereotypical images, mainly formed on the basis of Positivistic and Marxist literature.